The Role of the Vedomosti Newspaper in the Process of Improving Public Administration and the Development of the Public Service System in 1703–1725 - M. N. Kim; I. E. Yerykalova; S. A. Oskin (Управленческое консультирование, 2022)
In a scientifc study conducted by teachers of the Department of Journalism and Media Communications of the Faculty of Social Technologies of the RANEPA, the importance of the frst Russian newspaper Vedomosti as a means of reﬂecting the main directions of the domestic and foreign policy of the Russian state was determined and the degree of its inﬂuence on the processes of public administration in Russia in the frst quarter of the XVIII century was revealed. To achieve the purpose of the study, an analysis of the content of all issues of Vedomosti for 1703–1727 was carried out, which made it possible to determine the functional tasks of this publication for the formation of public opinion, propaganda among the social elite of the need for political, social, economic and cultural transformations in the country, including in the feld of public service and public administration. Since the era of Peter the Great, the formation of the information space of Russia began, which had a direct impact on the processes of public administration, on the development of the public administration’s system and on the creation of mechanisms for the state personnel policy of Russia. It is known that the editor of a number of issues of Vedomosti and the author of some articles was Peter I, which made the newspaper a state media outlet. The experience of publishing Peter’s Vedomosti has shown how important not only the informational, but also the agitation and propaganda function is for the state media of modern Russia.